Die sozialen Kämpfe in Südafrika verbinden? Gewerkschaften und soziale Bewegungen im Bündnis gegen prekäre Beschäftigung und die Kommodifizierung öffentlicher Güter - Ludwig, Carmen (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2013)
After the end of Apartheid 18 years ago, class conflicts are on the rise in South Africa. In most cases, social struggles of poor communities and trade union protests are led separately from each other. In contrast, trade unions in South Africa were regarded as an exemplar of Social Movement Unionism in their fight against Apartheid. Based on seven interviews and three group discussions with trade unionists from the South African Municipal Workers’ Union (SAMWU) and municipal employees in Cape Town, this article examines the impact, chances and obstacles of coalition building between trade unions and the new social movements in contemporary South Africa. In Cape Town SAMWU and social movements are working together to formulate an alternative Development Plan for the city as well as joint ideas for a good public service based on the needs of poor communities. As casualisation is increasing and undermining the associational power of trade unions, links are rebuild between SAMWU and community organisations in Cape Town. At the same time it can be shown that the joining of forces and social struggles is based on preconditions and needs intensified efforts undertaken by unions and social movements alike.